THU0550 Early Multidisciplinary Interventions To Promote Work Participation in People with Regional Musculoskeletal Pain: A Systematic Review. (15th July 2016) - Cochrane, A.; Higgins, N.M.; FitzGerald, O.; Gallagher, P.; Ashton, J.; Breen, R.; Brennan, A.; Corcoran, O.; Desmond, D.
Abstract : Background: Musculoskeletal disorders are amongst the leading causes of disability in the working age population. Whilst there is a growing body of evidence suggesting that early targeted multidisciplinary interventions can promote work retention and prevent disability, the evidence is far from conclusive as to which interventions are the most effective. Objectives: To review randomised controlled trials evaluating the effectiveness of early interventions in promoting work participation in adults with regional musculoskeletal pain (RMSKP). Methods: CENTRAL, MEDLINE, EMBASE, Scopus, PEDro and OT Seeker (1990 to April 2015) were searched. Reference lists of identified articles and reviews were hand searched. Only RCTs reporting on work-related outcomes were eligible for inclusion. The intervention had to include two or more elements of the biopsychosocial model delivered as an integrated programme. Participants were either experiencing difficulties at work or had less than three months sick leave as a result of their RMSKP at enrolment. Each RCT was assessed independently by two reviewers for risk of bias. Results were analysed by hazard ratios for return to work data, while continuous outcomes were analysed as mean difference (MD) with 95% confidence intervals. Results: 19 RCTS were included; the considerable variation in the components employed in the interventions limited the option to pool the data statistically using meta-analysis. There was some evidence that programmes involving a stepped care approach (4 studies) increased the probability of return to work at the 12-month follow-up [HR 1.29 (95% CI, 1.03 to 1.61), p=0.03]. However, preliminary analyses indicate a lack of consistent evidence for effects on reducing sickness absences, pain reduction and functional improvement across the intervention types. Conclusions: The lack of agreement as to what constitutes "early" in the context of treating RMSKP may have contributed to the rather ambiguous findings. In addition, the different health and social insurance systems across the trials have made it difficult to generalise the results. There remains a need to establish the active components that promote work retention in this population, and to identify the patients who are most likely to benefit from an integrated and cost-effective intervention. Disclosure of Interest: None declared